2018
DOI: 10.1371/journal.pntd.0006645
|View full text |Cite
|
Sign up to set email alerts
|

Grade 2 disabilities in leprosy patients from Brazil: Need for follow-up after completion of multidrug therapy

Abstract: BackgroundLeprosy continues to be a public health problem in many countries. Difficulties faced by health services include late diagnosis, under-reporting of new cases, adequate monitoring of disabilities and treatment. Furthermore, systematic follow-up after completion of treatment is important, when new disabilities may occur, or existing disabilities may get worse. The objective of the present study was to determine the prevalence of leprosy-associated grade 2 disabilities (G2D) after completion of multidru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
47
0
18

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 36 publications
5
47
0
18
Order By: Relevance
“…It is worth noting that this study also found a strong relationship between the evolution to disability with multibacillary forms, as well as the correlation between disease chronicity and the presence of leprosy reactions, in agreement with the data found in the present study. [20] Moreover, among the group of patients with involvement of the right tibial and ulnar nerves, 50% of patients who did not improve after MDT evolved with leprosy reaction. This observation demonstrates what had already been observed by Kamath et al (2014) [16], who states that reactions play an important role in the chronicity of Hansen's disease and is another reason for long-term follow-up of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that this study also found a strong relationship between the evolution to disability with multibacillary forms, as well as the correlation between disease chronicity and the presence of leprosy reactions, in agreement with the data found in the present study. [20] Moreover, among the group of patients with involvement of the right tibial and ulnar nerves, 50% of patients who did not improve after MDT evolved with leprosy reaction. This observation demonstrates what had already been observed by Kamath et al (2014) [16], who states that reactions play an important role in the chronicity of Hansen's disease and is another reason for long-term follow-up of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Higher education has been shown to be associated with better understanding of the disease and, consequently, better access and utilization of health services. Regular treatment and evaluation, as well as self-care, are aspects that prevent the worsening of leprosy cases [17,25].…”
Section: Discussionmentioning
confidence: 99%
“…La ENL presenta una frecuencia del 50% en pacientes con LL y del 5-10% en lepra borderline [15] . La importancia de las lepro-reacciones radica en que son la principal causa de daño axonal nervioso y, por ende, de discapacidad [17] .…”
Section: Discussionunclassified
“…La EH se ha relacionado a distintos grados de discapacidad y desempleo, especialmente en pacientes con lepro-reacciones y engrosamiento o afección de la sensibilidad de nervios troncales [17] . En el 2003, la OMS clasificó los grados de discapacidad en Grado 0: sensibilidad conservada, no alteraciones visuales; Grado 1: alteraciones sensitivas, no alteración visual; y Grado 2: alteraciones sensitivas y visuales [18] .…”
Section: Discussionunclassified